Production of a starch-based polymeric coating with incorporation of bioactive principles from chemical synthesis to extend the shelf life of cavendish banana (2024)
Crown rot is a severe postharvest disease affecting tropical and subtropical fruits like mango, avocado, papaya, and banana. It is caused by fungal pathogens that penetrate the fruit, reducing its pulp and leading to premature ripening. Systemic fungicides have been used to control these fungi, typically applied to seeds, leaves, or fruits to prevent disease spread. However, traditional fungicides can pose toxicity risks to the environment and human health. Essential oils are chemical substances that can be found in plants and have antifungal capacity. Essential oils are being investigated as an alternative to traditional fungicides since they are less toxic to the environment and human health; however, they are more expensive and less efficient than traditional fungicides. Accordingly, chemically synthesizing the chemical compounds that are the active antifungal agent inside essential oils can be an ecological and effective approach to produce a new generation of antifungals. In this study, modified starch was investigated as a carrier for thymol (active antifungal agent in thyme oil) incorporation using four distinct methods. Emulsions of starch and thymol were prepared and spray dried to obtain a soluble powder that was used to produce coatings. The most effective method for thymol incorporation yields a retention of approximately 40% according to gas chromatography analysis. In-vitro results indicated that thymol incorporated into the matrix exhibited antifungal effects against key fungi responsible for crown rot disease in Cavendish bananas at concentrations greater than 6% w/w relative to the coating matrix.